PVB (Polyvinyl Butyral) film for PDLC (Polymer Dispersed Liquid Crystal) dimming glass, preparation method and PDLC dimming glass

By using benzoic acid ester plasticizers in PDLC dimming glass, the problem of plasticizer migration was solved, the stability of PVB film and the service life of PDLC dimming glass were improved, and the process flow was simplified and production efficiency was increased.

CN121022299APending Publication Date: 2025-11-28JIAXING FUYING COMPOSITE MATERIALS CO LTD

Patent Information

Application Number
CN202511161298.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

In existing PDLC dimming glass, the plasticizer triethylene glycol diisooctyl ester is prone to migration, resulting in transparent cut edges, which affects the privacy protection effect. In addition, the edge sealing process is cumbersome and has low production efficiency.

Method used

By replacing triethylene glycol diisooctanoate with benzoic acid ester plasticizers, the interaction with PVB is enhanced, steric hindrance is increased, and plasticizer migration is inhibited by introducing benzene rings, branches, and complex main chain structures.

Benefits of technology

It significantly improves the long-term stability and anti-migration properties of PVB film, extends the service life of PDLC dimming glass, simplifies the process flow, and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121022299A_ABST
    Figure CN121022299A_ABST
Patent Text Reader

Abstract

The invention relates to a PVB (Polyvinyl Butyral) film for PDLC (Polymer Dispersed Liquid Crystal) dimming glass, a preparation method and the PDLC dimming glass, and belongs to the technical field of dimming glass. The PVB film for the PDLC dimming glass comprises PVB resin and a plasticizer, at least one end group of the plasticizer is a benzoate group, and the plasticizer belongs to benzoate. Through molecular structure design, the main chain of the plasticizer can be a polyether type [-CH2-CHY-O-] n chain segment or a polyol skeleton, and meanwhile, benzoate groups or specific end group structures (such as branched chain alkyl, aromatic hydrocarbon and the like) are introduced, so that the interaction (such as hydrogen bond damage, dipole interaction, pi-pi accumulation and the like) between the plasticizer and PVB resin is enhanced, and the plasticizer can be used for preparing PVB resin. By introducing structures such as branched chains and aromatic rings, the steric hindrance and rigidity of molecules are greatly improved, and migration and precipitation phenomena of the plasticizer in the PVB film are effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a PVB film, in particular to a PVB film for PDLC dimming glass, a preparation method and PDLC dimming glass, belonging to the technical field of dimming glass. BACKGROUND

[0002] Dimming glass is a kind of glass that can switch between transparent and opaque states through electric control, light control, temperature control, etc. Among them, PDLC dimming glass realizes the adjustment of transparency through electric control, and becomes foggy when power off, which can protect the privacy of users and is widely used in building glass, indoor partition, car sunroof side window, etc. The structure of PDLC dimming glass is usually: glass / PVB film / PDLC dimming film / PVB film / glass.

[0003] The commonly used plasticizer of PVB film, triethylene glycol diisooctylate, is an amphiphilic small molecule substance. The triethylene glycol part has good hydrophilicity, and the octanoate part has good lipophilicity; it has good compatibility with PVB resin which has both polar and non-polar segments. Although it does not cause phase separation, triethylene glycol diisooctylate is unstable in PVB film and tends to migrate out of the surface of PVB film; at the same time, since the cutting edge of the PDLC dimming film directly contacts the PVB film, the liquid crystal layer is physically damaged at the cutting site, and the migrated plasticizer reacts with the liquid crystal material, which further causes the edge part to become transparent, and the corresponding area loses the dimming function, and there is a risk of user privacy leakage.

[0004] In view of the above defects, the conventional solution is to seal the edge of the PDLC dimming film to avoid direct contact between the PVB layer and the cutting edge of the PDLC dimming film.

[0005] For example, the invention patent with application number CN113671744A discloses a sealing process for a PDLC dimming film for car sunroof glass, which includes the following steps: S1, place the PDLC film piece with electrode grooves and non-electrode grooves on the glue table with the clean side facing up; S2, glue the electrode groove and non-electrode groove; S3, use a blade to scrape the glue on the edge of the groove; S4, place the PDLC film piece in the curing box for curing, and continue to seal the other side of the PDLC film piece with electrode grooves; S5, repeat the film inspection and cleaning steps of S1, the glueing step of S2 and the scraping step of S3, and secondary curing.

[0006] As the application patent with the application number CN117962431A discloses a laminated glass containing a PDLC film and a packaging method thereof, the laminated glass includes a sealing edge structure: a second sealing edge film is located between the lower edge surface of the PDLC film and the second adhesive layer; part of the first sealing edge film is located between the upper edge surface of the PDLC film and the first adhesive layer, the remaining part extends outward along the edge thickness surface of the PDLC film, the extension end surface of the second sealing edge film in sequence to form a step, and the part located on the extension end surface of the second sealing edge film is provided with an air hole; a top sealing edge film is located at the step and extends outward along the parallel direction of the edge surface of the PDLC film; a patch adhesive layer is located at the step; the packaging method includes the following steps: S1, according to the structure of the laminated glass containing the PDLC film, laminated stacking is carried out to obtain a laminated structure; S2, the laminated structure obtained in S1 is fixed, and then cold pumping is carried out to exhaust the air between the layers of the laminated structure; the cold pumping conditions include: the vacuum degree is 0.05-0.9 bar, and the cold pumping time is not less than 5 min; S3, the laminated glass after cold pumping is subjected to pre-positioning treatment, and the process of the pre-positioning treatment includes: the vacuum degree is controlled at 0.05 bar-0.9 bar, first kept at 81-85 DEG C for 5-15 min, then kept at 121-128 DEG C for 10-30 min, and then cooled; S4, the laminated glass after pre-positioning treatment is subjected to high-temperature and high-pressure treatment, and the process of the high-temperature and high-pressure treatment includes: first heated to 82-93 DEG C for 5-10 min, the pressure during the first heating and the heat preservation is controlled at 0.09-1.2 bar; then continuously heated to 140-145 DEG C for 40-60 min, the pressure during the second heating and the heat preservation is controlled at 10-12 bar, and then cooled, and the pressure gradually decreases during the cooling process.

[0007] But the sealing edge process prevents the cutting edge from directly contacting the PVB film, the process is complicated, and the production efficiency is low. SUMMARY

[0008] The present application solves the above problems and provides a PVB film for PDLC dimming glass.

[0009] The technical scheme for solving the above problems is as follows:

[0010] A PVB film for PDLC dimming glass, comprising PVB resin and plasticizer, the plasticizer is a benzoic acid ester substance meeting conditions 1), 2) or conditions 1), 3) or conditions 1), 4):

[0011] 1), one end group is benzoic acid ester group;

[0012] 2), the other end group is directly connected with the benzoic acid ester group, which is one of C6-C8 alkyl, phenyl, benzyl, phenethyl, phenylpropyl.

[0013] 3) The main chain is [–CH2–CHY-O–] n The other end group of the chain segment is selected from H, OH, C1~C8 alkyl, ester group formed from C1~C8 carboxylic acid, phenyl, benzyl, phenethyl, phenylpropyl, benzoate group; Y=H or CH3, n=2~20;

[0014] 4) The main chain is a polyol skeleton, and the remaining end groups are selected from one or more of H, OH, C1~C8 alkyl, ester group formed by C1~C8 carboxylic acid, phenyl, benzyl, phenethyl, phenylpropyl, and benzoate group.

[0015] In this invention, the main chain is [–CH2–CHY-O–]. n In the technical solution of the chain segment, when n is 1~3, the other end group is selected from one of C6~C8 branched alkyl, ester group formed from C6~C8 branched carboxylic acid, phenyl, benzyl, benzoate group. In the above technical solution, branched alkyl refers to an alkyl group whose carbon skeleton is not straight but has branches, such as isooctyl; branched carboxylic acid refers to a carboxyl group in the molecule, and the carbon atom (α-carbon) or higher carbon atom (β-carbon, etc.) connected to the carboxyl group has branches (such as methyl, ethyl, etc.), such as isooctanoic acid.

[0016] In this invention, the main chain is [–CH2–CHY-O–]. n In the technical solution of the chain segment, when n is 4~7, the other end group is selected from one of C3~C8 branched alkyl, ester group formed by C3~C8 branched carboxylic acid, phenyl, benzyl, phenethyl, phenylpropyl, benzoate group.

[0017] In this invention, the main chain is [–CH2–CHY-O–]. n In the technical solution of the chain segment, when n is 8~11, the other end group is selected from one of C1~C8 alkyl, ester group formed by C1~C8 carboxylic acid, phenyl, benzyl, phenethyl, phenylpropyl, benzoate group.

[0018] In this invention, the main chain is [–CH2–CHY-O–]. n In the technical solution of the chain segment, when n is 12~20, the other end group is selected from H, OH, C1~C8 alkyl, ester group formed by C1~C8 carboxylic acid, phenyl, benzyl, phenethyl, phenylpropyl, benzoate group.

[0019] In the technical solution of the present invention where the main chain is a polyol skeleton, when the number of carbon atoms in the polyol skeleton is 3 to 5, the remaining end groups are selected from one or more of C6 to C8 branched alkyl groups, ester groups formed from C6 to C8 branched carboxylic acids, phenyl, benzyl, phenethyl, phenylpropyl, and benzoate groups.

[0020] In the technical solution of the present application, when the number of carbon atoms of the polyol skeleton is 5-8, the remaining end groups are selected from one or more of C3-C8 branched alkyl, ester groups formed from C3-C8 branched carboxylic acids, phenyl, benzyl, phenethyl, phenylpropyl, benzoate groups.

[0021] In the technical solution of the present application, when the number of carbon atoms of the polyol skeleton is 9-20, the remaining end groups are selected from one or more of H, OH, C1-C8 alkyl, ester groups formed from C1-C8 carboxylic acids, phenyl, benzyl, phenethyl, phenylpropyl, benzoate groups.

[0022] In the prior art, triethylene glycol diisooctanoate (3G8) has the problem of easy migration. That is, the phenomenon of gradually diffusing, exuding to the surface from the PVB matrix, and even migrating to other materials in contact with it during use. The inventors analyzed that it may be based on the following reasons:

[0023] 1. 3G8 is a straight-chain or nearly straight-chain ester, with weak intermolecular forces, low molecular polarity, and high flexibility, which is easy to diffuse in the PVB matrix;

[0024] 2. The straight-chain plasticizer has weak interaction with the polar groups (such as hydroxyl groups) of PVB, lacks effective "anchoring" or "binding", and is easy to be "pushed" out;

[0025] 3. The influence of glass transition temperature, if the plasticizer is too flexible, it is easy to precipitate after temperature change or long-term use;

[0026] 4. Surface energy difference, concentration gradient, etc. will promote the enrichment and migration of the plasticizer to the surface.

[0027] When solving the above problems, the present application introduces benzene rings, branched chains, complex main chains (such as polyether chains, polyol skeletons), and specific end groups (such as benzoate groups, branched alkyl / carboxylate groups, etc.), so that the plasticizer molecules have: stronger interaction with PVB (such as dipole-dipole, π-π stacking, hydrogen bonding, etc.); larger molecular volume / steric hindrance (hinders migration); higher molecular polarity or rigidity (reduces fluidity); better anchoring effect (forms stronger bonds with polar groups in PVB); so that the plasticizer is not easy to diffuse out of the PVB matrix, thereby inhibiting migration.

[0028] In the above technical solution of the present application, one necessary condition is to contain at least one benzoate group. The benzoate group (–COO–Ph) is an aromatic ester group, which has the following characteristics: the π electron cloud of the benzene ring can produce π-π interaction or dipole interaction with the group in PVB; the polarity of the ester group is higher than that of the straight-chain alkyl group, and has stronger hydrogen bonding or dipole interaction with the hydroxyl group and acetoxy group in PVB; the aromatic structure increases the rigidity of the molecule and reduces the chain segment movement ability to inhibit migration. That is, by increasing the interaction with the PVB macromolecule and enhancing the steric hindrance, migration is inhibited.

[0029] In the above technical solution of the present application, another necessary condition is to select one of 2), 3) and 4). The main chain is [–CH2–CHY-O–] n (i.e. polyether segment, similar to polyethylene glycol skeleton) scheme:

[0030] When n = 1~3 (short chain), the other end group is selected from branched alkyl / branched carboxylate / aromatic group (phenyl, benzyl, etc.). In this case, the combination of “short chain + branched / aromatic end group” has moderate molecular weight but complex structure, which has both flexibility and steric hindrance to limit migration;

[0031] When n = 4~7 (medium chain length), n = 8~11, n = 12~20 (long chain), the branched structure (such as isopropyl, tert-butyl, etc.) increases the steric hindrance and reduces the molecular sliding ability, and the end group can gradually transition from branched to linear, and then to H / OH. With the change of chain length, the balance between molecular flexibility and interaction is adjusted; long chain but with benzene ring / branched ester group, which still provides good anchoring and steric hindrance. That is, the chain length and branched / aromatic ring are adjusted to optimize the molecular fluidity and interfacial bonding force.

[0032] As a preferred embodiment of the above technical solution, the benzoate substance is selected from at least one of benzyl benzoate, isooctyl benzoate, diethylene glycol dibenzoate, diethylene glycol isooctyl benzoate, triethylene glycol dibenzoate, triethylene glycol isooctyl benzoate, glycerol tribenzoate, glycerol isooctyl benzoate, trimethylolpropane tribenzoate, trimethylolpropane isooctyl benzoate, pentaerythritol tetrabenzoate, pentaerythritol isooctyl benzoate, sucrose benzoate, and sucrose isooctyl benzoate.

[0033] As a preferred embodiment of the above technical solution, the glycerol isooctyl benzoate is selected from at least one of glycerol diisooctyl benzoate and glycerol diisooctyl benzoate.

[0034] As a preferred embodiment of the above technical solution, the trimethylolpropane isooctyl benzoate is selected from at least one of trimethylolpropane diisooctyl benzoate and trimethylolpropane diisooctyl benzoate.

[0035] As a preferred embodiment of the above technical solution, the pentaerythritol benzoic acid iso-octanoic acid ester is at least one of pentaerythritol tri-benzoic acid iso-octanoic acid ester, pentaerythritol di-benzoic acid di-iso-octanoic acid ester, and pentaerythritol benzoic acid tri-iso-octanoic acid ester.

[0036] As a preferred embodiment of the above technical solution, the sucrose benzoic acid iso-octanoic acid ester is an organic compound in which at least one of the eight hydroxyl groups of a sucrose molecule is esterified with benzoic acid, and the remaining hydroxyl groups are esterified with iso-octanoic acid.

[0037] In the above technical solution, the triethylene glycol benzoic acid iso-octanoic acid ester is a double ester formed by one molecule of triethylene glycol, one molecule of benzoic acid, and one molecule of iso-octanoic acid. Specifically, one end of the triethylene glycol is esterified with the carboxyl group of the benzoic acid through a hydroxyl group, and the other end is esterified with the carboxyl group of the iso-octanoic acid through a hydroxyl group. The same applies to other substances such as trimethylolpropane benzoic acid iso-octanoic acid ester and pentaerythritol benzoic acid iso-octanoic acid ester.

[0038] As a preferred embodiment of the above technical solution, the addition amount of the plasticizer is 20-50% of the mass of the PVB resin.

[0039] In the above technical solution, when the addition amount of the plasticizer is less than 20%, the intermolecular hydrogen bond network of the PVB cannot be sufficiently weakened, resulting in a PVB film that is still relatively hard, brittle, and has poor processing flowability. When the addition amount of the plasticizer exceeds 50%, the PVB resin matrix is excessively "diluted", the mechanical strength of the PVB significantly decreases (tensile strength and modulus decrease), the thermal stability deteriorates (softening point decreases and the PVB easily flows at high temperatures), and the plasticizer is prone to migration / exudation (especially for linear or low-interaction plasticizers). That is, 20% is the "minimum effective dose" to ensure the basic flexibility, processability, and adhesion of the PVB; 50% is the "reasonable upper limit" to avoid the negative effects of the plasticizer while ensuring good processability, flexibility, and functionality; and 20-50% is the range that achieves the best balance between flexibility, processability, adhesion, functionality, and stability.

[0040] Another object of the present application is to provide a preparation method of the above PVB film.

[0041] A preparation method of a PVB film for PDLC dimming glass, comprising the steps of stirring and uniformly mixing the PVB resin and the plasticizer, and then extruding and casting the mixture into a PVB film sheet using a screw extruder.

[0042] As a preferred embodiment of the above technical solution, the thickness of the PVB film sheet is controlled to be 0.2-0.5 mm.

[0043] Another object of the present application is to provide a PDLC dimming glass.

[0044] The PDLC dimming glass comprises a first light-transmitting plate, a first PVB film, a PDLC dimming film, a second PVB film and a second light-transmitting plate which are sequentially stacked, and the first PVB film and the second PVB film are prepared by the above method.

[0045] In summary, the present application has the following advantages:

[0046] 1、The application uses a special structure of benzoate plasticizer to replace the traditional linear plasticizer (such as 3G8) which is easy to migrate, which significantly improves the application performance and long-term stability of PVB film in PDLC dimming glass. The main chain of the benzoate plasticizer can be polyether type [–CH2–CHY-O–] n segment or polyol skeleton, while introducing benzoate group and specific end group structure (such as branched alkyl, aromatic hydrocarbon group, aromatic ester group, etc.), which not only enhances the interaction between the plasticizer and PVB resin (such as hydrogen bond, dipole interaction, π-π stacking, etc.), but also greatly improves the steric hindrance and rigidity of the molecule by introducing branched chain and aromatic ring, effectively inhibiting the migration and precipitation of the plasticizer in the PVB film. At the same time, the addition amount of the plasticizer is controlled in the range of 20% to 50% of the mass of the PVB resin, which ensures that the PVB film has good flexibility, processing fluidity and adhesion, and the finally prepared PVB film not only has excellent mechanical properties, but also significantly improves the durability, anti-migration and stability during long-term use, prolonging the service life of the PDLC film; the edge transparent range of the prepared PDLC dimming glass is small, the migration rate of the plasticizer to the inside of the PDLC film is slowed down, and the service life, appearance retention and comprehensive performance of the PDLC dimming glass are improved as a whole;

[0047] 2、The benzoate as a plasticizer for PVB significantly increases the tensile strength and Young's modulus of the PVB film, improving the mechanical properties of the PVB;

[0048] 3、The PDLC dimming glass of the present application has a simple process flow, high production efficiency, important application value and industrialization prospect. BRIEF DESCRIPTION OF DRAWINGS

[0049] Figure 1 is a structural schematic diagram of the PDLC dimming glass in Example 1;

[0050] Figure 2 is a partial enlarged view of Figure 1 ;

[0051] In the figure, the components represented by each reference numeral are as follows:

[0052] 1 - first light-transmitting plate,

[0053] 2- First PVB membrane,

[0054] 3-PDLC dimming film,

[0055] 4-Second PVB film,

[0056] 5-Second light-transmitting plate. Detailed Implementation

[0057] The present invention will be further explained and described below with reference to the accompanying drawings.

[0058] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. Any changes made by those skilled in the art after reading this specification, as long as they fall within the scope of the claims, will be protected by patent law.

[0059] Example 1

[0060] A PVB film comprising PVB resin and a plasticizer. Specifically, 40g of PVB resin and 15.17g of trimethylolpropane tribenzoate plasticizer.

[0061] The PVB resin has a degree of polymerization of 599~2199. In this embodiment, polyvinyl butyral resin PVB_18K18 is preferred. PVB_18K18 refers to PVB molecules with a degree of polymerization of approximately 1800 and an -OH content of approximately 18wt%.

[0062] Trimethylolpropane tribenzoate, CAS No. 54547-34-1; structural formula as follows:

[0063] .

[0064] Specifically, the preparation method of this PVB film is as follows:

[0065] Mix 40g of PVB resin powder and 15.17g of trimethylolpropane tribenzoate evenly, and then extrude and cast into a PVB film with a thickness of 0.38mm.

[0066] A type of PDLC dimming glass, such as Figure 1~2 As shown, the structure includes a first light-transmitting plate 1, a first PVB film 2, a PDLC dimming film 3, a second PVB film 4, and a second light-transmitting plate 5, which are stacked sequentially. Both the first light-transmitting plate 1 and the second light-transmitting plate 5 are float glass; the first PVB film 2 and the second PVB film 4 are prepared using the aforementioned PVB film preparation method.

[0067] In the process of preparing PDLC switchable glass, the first light-transmitting plate (usually glass), the first PVB film, the PDLC switchable film, the second PVB film, and the second light-transmitting plate (glass) are stacked in a specific order, and then subjected to a high-temperature and high-pressure autoclave process to make the layers tightly bonded together, while the air between the layers is discharged, and finally a stable structure, optically transparent and with light-adjusting function is formed. The following is the operation of this process.

[0068] First, prepare two pieces of glass with good light transmission performance and smooth surface without scratches as the first light-transmitting plate and the second light-transmitting plate. The material is usually selected from float glass or ultra-white glass, with a thickness range of 4 mm to 8 mm, commonly 6 mm. The glass edges are recommended to be chamfered to reduce the risk of stress concentration in subsequent use. At the same time, prepare two pieces of polyvinyl butyral (PVB) interlayer film as the bonding layer, as the first PVB film and the second PVB film respectively. The recommended thickness is 0.38 mm. The PVB film should have good optical transparency, flexibility and bonding performance. Before use, it needs to be ensured that its surface is clean, free of creases and dust, and stored in a dry environment to avoid moisture absorption. The PDLC switchable film, as the core part of the light-adjusting function, is usually a pre-formed film, which contains liquid crystal droplets, polymer matrix and two layers of transparent conductive film (such as ITO conductive film). Its thickness is generally between 0.7 mm and 1.1 mm. The film requires high requirements for surface cleanliness and operating environment, and should be handled with gloves to avoid scratches, fingerprint pollution and moisture. Usually, a protective film is attached to the surface when it is delivered, and it should be removed before stacking to avoid long exposure time.

[0069] After the materials are prepared, the layer assembly process begins. In a clean and dust-free operating environment, place the layers in the following order from bottom to top: first place the second light-transmitting plate (glass) as the bottom layer; then place the second PVB film on top of the second light-transmitting plate, keeping it centered and leaving a uniform margin around the edges, usually 5 to 10 mm on each side, to prevent PVB overflow during the subsequent lamination process; then place the PDLC switchable film on top of the second PVB film, also keeping it centered and aligned to ensure that the relative position of the light-adjusting area and the glass edge meets the design requirements; then place the first PVB film, which should be the same size as the second PVB film to ensure symmetry and balance of the overall structure; finally, place the second light-transmitting plate (glass) as the top layer to complete the stacking of the five layers. After stacking, a soft rubber roller or a special pressure roller can be used to gently roll from the center to the edges of the stack to preliminarily remove any large bubbles that may exist between the layers, improving the stability of the subsequent lamination process. If conditions permit, the stack can also be pre-vacuumed to further reduce bubble residue and improve lamination quality.

[0070] To further improve the lamination effect, the five-layer structure is subjected to cold pressing pretreatment before entering the autoclave. The stack is placed in the cold pressing equipment, the temperature is set to 60°C, the pressure is 0.5 MPa, and it is maintained for 10 min. This step helps to preliminarily compact the materials, reduce air bubbles, and enhance the preliminary adhesion between the PVB film and the glass and between the PVB film and the PDLC film, creating more ideal conditions for subsequent high-temperature and high-pressure lamination and reducing the risk of defects during the lamination process.

[0071] After cold pressing pretreatment, the stack structure can be placed in the autoclave for core lamination process (or directly enter the lamination process).

[0072] During the lamination process, the PVB film melts and flows under the combined action of high temperature and high pressure, fully filling the small gaps between the layers and expelling residual air, while achieving firm bonding between PVB and glass and between PVB and PDLC film. The recommended high-temperature and high-pressure process parameters are as follows: the temperature in the autoclave is raised to 145°C, which can ensure that the PVB film is fully softened and has good fluidity, while avoiding decomposition of the material due to excessive temperature; at the same time, a pressure of 1.0-1.2 MPa is applied to the autoclave to ensure uniform pressure on all parts of the stack, promoting the PVB film to flow fully and expel air bubbles, achieving tight adhesion between the layers; the above temperature and pressure conditions are maintained for 60 min to ensure that the PVB is completely fused, air bubbles are fully expelled, and the interlayer bonding is firm and stable. During the temperature and pressure increase process, a gradual approach should be adopted to avoid sudden changes in temperature and pressure that may cause impact on the glass or film layers; after the holding time, the temperature and pressure are reduced, which should be done slowly to ensure that the temperature in the autoclave is reduced to below 50°C and the pressure is basically released to normal pressure before the autoclave door is opened to remove the laminated glass product.

[0073] The removed PDLC dimming glass needs to be checked for appearance and function. The qualified product should have no bubbles, delamination, white spots or other optical defects, good edge sealing, uniform light transmission, and good optical transparency. The electrical control function of the PDLC dimming film can then be tested by connecting the appropriate drive circuit to verify its dimming performance, including switch response, haze change, transmittance adjustment range, and response speed, to ensure normal and stable dimming function. If PVB overflow edges are reserved around the stack, the edges can be trimmed as needed to improve the neatness and safety of the product appearance. In addition, to ensure the quality of the final product, it is recommended to inspect each piece of dimming glass one by one to exclude products with obvious defects and ensure consistency.

[0074] Supplementary note: In actual production process, the temperature, pressure and time parameters of high temperature and high pressure lamination can be adjusted appropriately according to the specific equipment performance, material characteristics and product requirements, so as to achieve the best lamination effect. For high-transmittance, high-reliability or special-purpose PDLC light control glass, further optimization can also be carried out on material selection, layering sequence or post-processing process. The entire process flow has high requirements for environmental cleanliness, operation standardization and equipment stability, and it is recommended to be executed in a production environment with corresponding conditions to ensure product quality and yield.

[0075] Example 2

[0076] The difference between this example and Example 1 is only that the type of plasticizer is different (the amount remains the same).

[0077] In this example, glycerol tribenzoate is selected as the plasticizer.

[0078] Glycerol tribenzoate, CAS No. 614-33-5; the structural formula is as follows:

[0079] .

[0080] Example 3

[0081] The difference between this example and Example 1 is only that the type of plasticizer is different (the amount remains the same).

[0082] In this example, sucrose benzoate is selected as the plasticizer.

[0083] Sucrose benzoate, CAS No. 12738-64-6; the structural formula is as follows:

[0084] .

[0085] Example 4

[0086] The difference between this example and Example 1 is only that the type of plasticizer is different (the amount remains the same).

[0087] In this example, pentaerythritol tetrabenzoate is selected as the plasticizer.

[0088] Pentaerythritol tetrabenzoate, CAS No. 4196-86-6; the structural formula is as follows:

[0089] .

[0090] Example 5

[0091] The difference between this example and Example 1 is only that the type of plasticizer is different (the amount remains the same).

[0092] In this example, diphenic acid dipolypropylene glycol ester is selected as the plasticizer.

[0093] Dipropylene glycol dibenzoate, CAS No. 27138-31-4, structure as follows:

[0094] .

[0095] Example 6

[0096] The difference between this example and Example 1 is only that the type and amount of plasticizer are different.

[0097] In this example, the plasticizer is selected to be dipropylene glycol dibenzoate (CAS No. 27138-31-4) and trimethylolpropane tribenzoate (CAS No. 54547-34-1).

[0098] Among them, the amount of dipropylene glycol dibenzoate is 9.10 g; the amount of trimethylolpropane tribenzoate is 6.07 g; the total amount of plasticizer is consistent with Example 1.

[0099] Example 7

[0100] The difference between this example and Example 1 is only that the type of plasticizer is different (the amount is consistent).

[0101] In this example, the plasticizer is selected to be benzyl benzoate, CAS No. 120-51-4, structure as follows:

[0102] .

[0103] Example 8

[0104] The difference between this example and Example 1 is only that the type of plasticizer is different (the amount is consistent).

[0105] In this example, the plasticizer is selected to be triethylene glycol benzoate isooctanoate, structure as follows:

[0106] .

[0107] Example 9

[0108] The difference between this example and Example 1 is only that the type of plasticizer is different (the amount is consistent).

[0109] In this example, the plasticizer is selected to be pentaerythritol diisooctyl dibenzoate, structure as follows:

[0110] .

[0111] Comparative Example 1

[0112] The difference between this example and Example 1 is only that the type of plasticizer is different (the amount is consistent).

[0113] In this embodiment, the plasticizer is selected to be triethylene glycol diisooctylate, and the structural formula is as follows:

[0114] .

[0115] The effect of benzoic acid ester plasticizers is verified by the following tests.

[0116] The purpose of this test is to systematically evaluate the actual effect of the new material system in slowing down the diffusion of plasticizers, reducing the migration rate, and improving the overall mechanical properties and long-term stability of PVB films and PDLC dimming films by using benzoic acid ester plasticizers instead of traditional isooctanoate plasticizers, thereby providing scientific basis and technical support for the preparation of high durability, high optical stability, and long service life of PDLC laminated glass.

[0117] I. Thermal stability test

[0118] The main purpose of this test is to verify the application performance of benzoic acid ester plasticizers in PVB films, focusing on their improvement over traditional isooctanoate plasticizers (such as 3G8) in the following aspects:

[0119] Inhibiting the migration and precipitation of plasticizers, especially the concentrated precipitation in the edge area, slowing down the diffusion of plasticizers to the interface of PDLC dimming film, and avoiding the resulting failure of dimming function (such as local transparency, abnormal haze, and drive failure, etc.);

[0120] By comparing the performance of PDLC laminated glass samples using traditional plasticizers and benzoic acid ester plasticizers in heat treatment, the advantages of benzoic acid ester plasticizers in improving the overall performance of the product are clarified.

[0121] 1. Basic materials

[0122] Glass substrate: Selecting float glass with a thickness of 6 mm, both sides are flat and free of scratches, and the edges are chamfered;

[0123] PVB interlayer film: provided by Examples 1-9 and Comparative Example 1;

[0124] PDLC dimming film: Selecting standard PDLC film containing liquid crystal droplets, polymer matrix and ITO conductive layer, with a thickness of about 0.8 mm, and having basic electrically controlled dimming function;

[0125] Plasticizer:

[0126] Traditional plasticizer (Comparative Example 1): triethylene glycol diisooctylate (3G8), as a control group;

[0127] Test plasticizer (Examples 1~9): Special structure benzoate plasticizer, as a test group; Branched structure, aromatic ring group and larger steric hindrance, molecular design to enhance the interaction with PVB resin and inhibit migration.

[0128] 2、Sample structure

[0129] All test samples use a five-layer structure, from bottom to top in turn:

[0130] That is: glass / PVB (containing plasticizer) / PDLC / PVB (containing plasticizer) / glass.

[0131] Each plasticizer system prepares 3 groups of parallel samples for subsequent performance comparison and data reliability verification.

[0132] 3、Test method

[0133] 3.1 Sample preparation

[0134] According to the standard process, glass, PVB film (containing specified plasticizer), PDLC dimming film are stacked in turn, after cold pressing pretreatment, put into high temperature and high pressure kettle for lamination. The lamination parameters are set as: temperature 140°C ± 2°C, pressure 1.1 MPa ± 0.1 MPa, holding time 45 minutes, then slowly cool down to normal pressure and room temperature, then take out the sample.

[0135] The prepared PDLC laminated glass sample is placed in the standard environment (temperature 23±2℃, relative humidity 50%±5%) for more than 24 hours to reach the stable state of performance, and then enters the test and aging link.

[0136] 3.2 Comparison test design

[0137] Two groups of comparison samples are set:

[0138] Control group: PVB uses traditional isooctanoate plasticizer (such as 3G8);

[0139] Test group: PVB uses benzoate plasticizer;

[0140] The other process parameters (such as PVB thickness, PDLC type, lamination conditions, etc.) of the two groups of samples are kept consistent, only the plasticizer type is replaced, to exclude the interference of other variables.

[0141] 3.3 Accelerated aging and performance test

[0142] In order to simulate the effects of thermal oxidation, ultraviolet exposure and stress in long-term use environment, the following treatments and tests are carried out on the two groups of samples:

[0143] Conditions: Place the samples in 70°C environment for different time (e.g. 24 h, 72 h, 168 h), observe the edge "transparency" phenomenon and the change of light control area; evaluate the migration tendency of plasticizer under high temperature condition and the influence on the function of PDLC.

[0144] 4. Data collection

[0145] In each test, the system records the following information:

[0146] The edge transparency degree response effect of the control group and the test group samples after different time periods of heat treatment;

[0147] By visual observation, record the appearance time and degree of edge "whitening", local transparency, bubble or delamination phenomenon;

[0148] Compare the performance decay rate and appearance change degree of the two groups of samples within the same test period, to evaluate the difference between plasticizer migration and material aging.

[0149] 5. Test result analysis

[0150] The results are shown in Table 1.

[0151] Table 1 Performance comparison of different plasticizer systems in heat treatment test

[0152] Table explanation:

[0153]

[0154] Transparent part distance from PDLC cutting edge: refers to the distance from the actual functional edge (or cutting edge) of the PDLC light control film to the glass substrate, where the optical transparent or whitening (low haze, non-light control response) area appears, which is a key indicator to measure the diffusion degree of plasticizer to the PDLC interface;

[0155] Day 1: record the initial state, all samples should have no transparent part (i.e. distance 0 mm) in normal state;

[0156] Day 3 and Day 7: the samples are heat treated in 70°C environment, observe whether the edge area appears whitening or transparency phenomenon due to plasticizer migration, and the expansion degree of the phenomenon over time;

[0157] Comparative Example 1 (triethylene glycol diisooctylate): as a traditional plasticizer control group, it shows the fastest migration speed and the largest transparent area expansion, reaching 3.0 ~ 4.0 mm on the seventh day, indicating that the light control function and optical consistency are significantly affected;

[0158] Examples 1 ~ 9 (benzoate or plasticizer containing benzoate structure):

[0159] Examples 1, 3, 4, 6 show excellent performance, with a transparent area of 0-0.3 mm on the seventh day, indicating that they effectively inhibit the interfacial diffusion of plasticizers, and are suitable for scenarios with high requirements for long-term stability and reliability of light modulation function;

[0160] Examples 2, 5, 7, 8, and 9, although better than Comparative Example 1, still show a transparent area of more than 0.4 mm on the seventh day, indicating that their migration inhibition ability is slightly weaker, but still significantly better than traditional isooctanoate plasticizers.

[0161] As can be seen from Table 1:

[0162] The traditional plasticizer (Comparative Example 1: triethylene glycol diisooctanoate) migrates the fastest under heat treatment conditions and has the most severe edge transparency, with a transparent area of 3-4 mm on the seventh day, posing a significant risk of failure of light modulation function and optical performance.

[0163] Benzoate plasticizers (especially Examples 1, 3, 4, and 6) exhibit excellent performance in inhibiting plasticizer migration due to their aromatic ring structure, multiple branches, large steric hindrance, or complex synergistic effect, with no transparent area (0-0.3 mm) on the edge on the seventh day, which can significantly improve the long-term stability and reliability of light modulation function of PDLC laminated glass.

[0164] Complex plasticizers (such as Example 6) and structurally stable aromatic esters (such as Example 7) also have good anti-migration performance, providing flexible options for formulation optimization and performance balance design.

[0165] Plasticizers containing isooctanoate structures or flexible segments (such as Examples 8 and 9) have improved significantly compared to traditional plasticizers, but still have a certain migration tendency, and are recommended to be used cautiously or further optimized in scenarios with ultra-high durability requirements.

[0166] II. Mechanical property test

[0167] When evaluating the impact of different types of plasticizers on the comprehensive performance of PDLC laminated glass, the mechanical properties (especially tensile strength and Young's modulus) of the PVB film as the intermediate bonding layer directly affect the overall strength, bonding reliability, and durability of the laminated glass.

[0168] This part of the test aims to test the tensile strength and Young's modulus of PVB films prepared under different plasticizer systems, and systematically compare:

[0169] The performance of traditional plasticizers (such as triethylene glycol diisooctanoate, Comparative Example 1) and benzoate plasticizers (Examples 1-9) in increasing or decreasing the mechanical strength of PVB films;

[0170] Effects of different plasticizers on the flexibility, bonding strength, tear resistance and deformation resistance of PVB film

[0171] Find the optimal plasticizer combination that has excellent anti-migration performance while maintaining good mechanical properties, and provide a basis for material selection in actual production.

[0172] 1. Sample preparation

[0173] From the PVB film (thickness about 0.38 mm) prepared from each example / comparative example, dumbbell-shaped tensile specimens (in accordance with GB / T 1040 standard) were cut according to the standard;

[0174] The samples were conditioned in a standard environment (temperature 23±2℃, relative humidity 50%±5%) for at least 24 hours before testing.

[0175] 2. Test equipment and conditions

[0176] An electronic universal material testing machine was used;

[0177] The tensile speed was set to 50 mm / min (standard tensile rate);

[0178] At least 3 parallel samples were tested for each plasticizer system, and the average value was taken as the final result;

[0179] Test items include:

[0180] Tensile strength: the maximum stress that the PVB film can withstand before breaking under tension, unit MPa;

[0181] Young's modulus: the stress-strain ratio of the material in the elastic deformation stage, reflecting the stiffness or hardness of the material, unit MPa.

[0182] 3. Data collection

[0183] The results are shown in Table 2.

[0184] Table 2 Effects of different plasticizers on the mechanical properties of PVB film

[0185] Brief introduction of plasticizer structure characteristics Tensile strength Young's modulus Comparative example 1 triethylene glycol diisooctylate 3G8 Traditional plasticizer, strong plasticizing effect but easy to migrate 20~22MPa 10~15MPa Example 1 trimethylolpropane tribenzoate Benzoate, branched chain + aromatic ring, large steric hindrance 28~30MPa 350~400MPa Example 2 glycerol tribenzoate Ester structure, moderate steric hindrance 27~29MPa 320~380MPa Example 3 sucrose benzoate Multi-modified hydroxyl, complex structure, extremely large steric hindrance 30~32MPa 400~450MPa Example 4 pentaerythritol tetrabenzoate Multi-functional group + high branched chain, large steric hindrance 30~32MPa 450~500MPa Example 5 diphenic acid dimeric propylene glycol ester Benzoic acid + polyether structure, certain flexibility 26~ 28MPa 300~350MPa Example 6 diphenic acid dimeric propylene glycol ester + trimethylolpropane tribenzoate Compound system, rigid and flexible 28~30MPa 320~370MPa Example 7 benzyl benzoate Aromatic ester, stable structure, but small molecular chain length 27~29 MPa 360~400MPa Example 8 triethylene glycol benzoate isooctylate Double ester structure 29~31MPa 300~350MPa Example 9 pentaerythritol diphenic acid diisooctylate Polyol skeleton + double ester structure 28~30MPa 320~360MPa

[0186] Table notes:

[0187] Tensile strength: reflects the "tensile breaking resistance" of the PVB film under stress; the higher the value, the more difficult the film is to break, but too high a strength may be accompanied by brittleness.

[0188] Young's modulus: reflects the "stiffness" or "hardness" of the PVB film; the higher the value, the harder and less likely to deform the film, but it can also affect flexibility and bonding adaptability.

[0189] Comparative Example 1 (traditional plasticizer) has a higher tensile strength but a lower Young's modulus, indicating that the film is softer and more likely to deform, and is prone to stress relaxation and migration during long-term use.

[0190] Example 4 (pentaerythritol tetraphenylate) has the highest Young's modulus (450-500 MPa), indicating that the film is the hardest and the structure is the most stable, but the tensile strength is slightly lower, which belongs to the "high stiffness and low ductility" type.

[0191] Examples 1, 6, 8, and 9 achieve a good balance between tensile strength and Young's modulus, maintaining a certain strength while having high rigidity and anti-migration properties.

[0192] From Table 2, it can be seen that:

[0193] Benzoate plasticizers (especially pentaerythritol tetraphenylate, sucrose benzoate, trimethylolpropane tribenzoate, triethylene glycol benzoate isooctanoate, pentaerythritol diisooctanoate dibenzoate, etc.) not only effectively inhibit plasticizer migration, but also significantly improve the rigidity and structural stability of PVB film (high Young's modulus), and are superior to traditional isooctanoate plasticizers in mechanical properties and anti-aging ability.

Claims

1. A PVB film for PDLC dimming glass, comprising PVB resin and a plasticizer, characterized in that: The plasticizer is a benzoic acid ester substance whose structural formula satisfies conditions 1) and 2), or conditions 1) and 3), or conditions 1) and 4). 1) One end group is a benzoate group; 2) The other end group is directly connected to the benzoate group and is one of C6~C8 alkyl, phenyl, benzyl, phenethyl, or phenylpropyl. 3) The main chain is [–CH2–CHY-O–] n The other end group of the chain segment is selected from H, OH, C1~C8 alkyl, ester group formed from C1~C8 carboxylic acid, phenyl, benzyl, phenethyl, phenylpropyl, benzoate group; Y=H or CH3, n=2~20; 4) The main chain is a polyol skeleton, and the remaining end groups are selected from one or more of H, OH, C1~C8 alkyl, ester group formed by C1~C8 carboxylic acid, phenyl, benzyl, phenethyl, phenylpropyl, and benzoate group.

2. The PVB film for PDLC dimming glass according to claim 1, characterized in that: The benzoic acid esters are selected from at least one of benzyl benzoate, isooctyl benzoate, diethylene glycol dibenzoate, diethylene glycol isooctyl benzoate, triethylene glycol dibenzoate, triethylene glycol isooctyl benzoate, glyceryl tribenzoate, glyceryl isooctyl benzoate, trimethylolpropane tribenzoate, trimethylolpropane isooctyl benzoate, pentaerythritol tetrabenzoate, pentaerythritol isooctyl benzoate, sucrose benzoate, and sucrose isooctyl benzoate.

3. The PVB film for PDLC dimming glass according to claim 2, characterized in that: The glyceryl benzoate isooctanoate is selected from at least one of glyceryl dibenzoate isooctanoate and glyceryl diisoctanoate.

4. The PVB film for PDLC dimming glass according to claim 2, characterized in that: The trimethylolpropane benzoate isooctanoate is selected from at least one of trimethylolpropane dibenzoate isooctanoate and trimethylolpropane diisoctanoate.

5. The PVB film for PDLC dimming glass according to claim 2, characterized in that: The pentaerythritol isooctyl benzoate is selected from at least one of pentaerythritol isooctyl tribenzoate, pentaerythritol diisoctyl benzoate, and pentaerythritol isooctyl tribenzoate.

6. The PVB film for PDLC dimming glass according to claim 2, characterized in that: The sucrose benzoate isooctanoate is an organic compound formed by at least one of the eight hydroxyl groups of a sucrose molecule forming an ester with benzoic acid, and the remaining hydroxyl groups forming an ester with isooctanoic acid.

7. The PVB film for PDLC dimming glass according to claim 1, characterized in that: The amount of plasticizer added is 20-50% of the mass of PVB resin.

8. The method for preparing a PVB film for PDLC dimming glass according to claim 1, characterized in that... The process includes the step of mixing the PVB resin and the plasticizer and then extruding and casting them into a PVB film using a screw extruder.

9. The preparation method according to claim 8, characterized in that: The thickness of the PVB film is controlled between 0.2 and 0.5 mm.

10. A PDLC dimming glass, comprising a first light-transmitting plate (1), a first PVB film (2), a PDLC dimming film (3), a second PVB film (4), and a second light-transmitting plate (5) stacked sequentially, characterized in that: The first PVB film (2) and the second PVB film (4) are prepared by the method according to claim 8 or 9.

Citation Information

Patent Citations

  • Edge sealing process of PDLC dimming film for automobile skylight glass

    CN113671744A

  • Laminated glass containing PDLC (Polymer Dispersed Liquid Crystal) film and packaging method thereof

    CN117962431A

Cited By

  • Intermediate film for dimming glass and application of intermediate film

    CN122011640A

  • Plasticizer and preparation and application thereof

    CN122127301A